Age impact on clinical risk factors does not justify the age related change in referral pattern for osteoporosis assessment—Data from the Aalborg University Hospital Record for Osteoporosis Risk Assessment (AURORA). Issue 3 (March 2015) - Andersen, Stig; Laurberg, Peter
Highlights Discrimination causes negative attitudes that influenced clinical care in some domains. Age discrimination in osteoporosis screening was documented recently. We report discrepancy between similar weight of clinical risk factors between age groups and a change in the prevalence of clinical risk factors leading to referral for osteoporosis, that Implies influence of age discrimination on clinical care in osteoporosis. Awareness of discrimination by age in osteoporosis assessment is lacking.